Lichen allelopathy: a new hope for limiting chemical herbicide and pesticide use. Issue 8 (3rd August 2021) - Kalra, Rishu; Conlan, Xavier A.; Goel, Mayurika
ABSTRACT: Agriculture development remains the most significant and integral part of the economic growth of any country with pests, such as plant pathogens, weeds, insects, nematodes and animal, imposing a major threat to the overall productivity. Approximately 25% of the total crop production worldwide is damaged due to these weeds, animal and microbial pest attacks and thus application of agrochemicals to enhance crop productivity has become an integral part of agriculture practices. Beyond their desired activity these chemical pesticides have been associated with side effects that their direct impact on human health, soil and water quality and the residue having immensurable impact on the environment. Due to the severe side effects associated with synthetic pesticides, integrated pest management crop health practices have been developed to use biological products with allelopathic activity as pesticides. Here, we review lichen diversity, allelopathic potential from different lichen species and the lichen metabolites involved in allelopathic interactions. This review also highlights the various modes of actions of lichen metabolites, which include the lichen-plant, lichen-herbivore, lichen-insect and lichen-microbe interactions. Furthermore, a crisp swot on the most promising lichen-derived allelochemical metabolites, their biosynthetic pathways and scope of metabolomics in lichenological research has been discussed.